GC‐MS Analysis of Various Phytoestrogens in Health Functional Foods - Kim, Yu Ra; Pyo, Hee Soo; Chung, Bong Chul; Moon, Myeong Hee; Lee, Jeongae (Bulletin of the Korean Chemical Society, 2017)
This study aimed to measure phytoestrogen contents in health functional foods (HFFs) to alleviate menopausal symptoms that are commercially available in South Korea. A sensitive and selective method using gas chromatography–mass spectrometry (GC‐MS) for the monitoring of 21 phytoestrogens was developed and fully validated. Phytoestrogens were extracted by liquid–liquid extraction using methyl tert‐butylether as the solvent. Food samples were enzymatically hydrolyzed with β‐glucuronidase/arylsulfatase. Before GC‐MS, the analytes were derivatized to their trimethylsilyl derivatives by incubation with N,O‐bis(trimethylsilyl)trifluoroacetamide with 1% trimethylchlorosilane for 30 min at 80°C. The calibration curves showed good linearity (r 2 > 0.99) in the range of interest for each analyte. The limits of detection and quantification of the 21 phytoestrogens were in the ranges of 0.5–20 and 1–50 ng/mL, respectively. The intra‐ and inter‐day precisions were all below 15.7%. These multivariate procedures were efficient in determining the optimal conditions using peak heights as responses.